Evaluation of TDMA Robustness in WirelessHART Networks - Winter, Jean; Pereira, Carlos Eduardo; Netto, Joao C.; Souza, Fernando A.; Costa, C. M.; Muller, I. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
Industrial wireless sensor networks are the next step in fieldbuses. In order to cope with harsh industrial environments, they must employ several mechanisms to increase reliability, to be comparable with cable-based networks. One of these mechanisms makes is the time division multiplexing as a medium access controller on data link layer, which prevents collisions within the network itself and provides real time communications. However, the use of such control mechanism implies on precise clock generation and maintenance, for the field devices to keep track of synchronized time slots. This paper presents a study related to clock source tolerances on WirelessHART protocol. A case study is conducted with a developed and certified WirelessHART field device, whose clock generator is depicted for the study. A fault condition in the clock generation for time division multiple access is created and tested within a topology controlled network. The results and conclusions revealed a possible catastrophic failure due to a faulty time source field device.